Tingkat Kepentingan dan Kinerja Sarana Wisata di Daya Tarik Wisata Batu Basurek di Kabupaten Tanah Datar - Hanafi Hanafi; Pasaribu Pasaribu (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Batu Basurek is one of the cultural tourist attractions in Tanah Datar Regency that has high historical value. As a tourist destination, Batu Basurek attracts both domestic and international tourists to learn more about the culture and historical heritage. However, the facilities at this location still do not meet the standards that should be possessed by a cultural tourist attraction. This research aims to analyze the level of importance and performance of tourist facilities in Batu Basurek.This research uses a quantitative descriptive method with a survey approach, where a questionnaire is used as a data collection tool. The analysis technique applied is Importance Performance Analysis (IPA) to measure the gap between the level of importance and the performance of tourist facilities. This research was conducted from January 14 to 20, 2025, with a total sample of 131 respondents.The research results show a gap between visitor expectations and the actual condition of the tourist facilities. The Total Suitability Index (TSI) of 152% indicates that the performance of the tourist facilities still needs improvement. Some attributes that require primary attention are hotels (69%) and prayer rooms, toilets, and trash bins (66%), as despite being considered important by visitors, their performance is still inadequate. Meanwhile, the friendliness of the community (73%) and restaurants (68%) show quite good performance and need to be maintained. Tourist attractions (62%) and souvenir shops (63%) provide quite high satisfaction levels, even though their importance levels are relatively lower. As for attributes like travel agents (61%) and information centers (61%), they are not the main priorities for improvement.